Analysis of a circular journal bearing lubricated with micropolar fluids including EHD effects. Issue 2 (2014) - ,
Abstract : Purpose – The performance of finite circular journal bearing lubricated with micropolar fluids taking into account the elastic deformation of the bearing liner is presented. The paper aims to discuss these issues.Design/methodology/approach – The modified Reynolds equation is obtained using the micropolar lubrication theory. The solution of the modified Reynolds equation is determined using finite difference technique. The static characteristics in terms of load‐carrying capacity, attitude angle, side leakage and friction coefficient for micropolar and Newtonian fluids are determined for various values of eccentricity ratio and different values of elastic coefficient.Findings – Compared with Newtonian fluids, the micropolar fluids produce an increase in the load‐carrying capacity and a reduction in the attitude angle, the friction factor and side leakage for both the rigid and deformable bearings.Originality/value – It is concluded that the influence of elastic deformation on the bearing characteristics lubricated with micropolar fluids is significantly apparent compared with bearing lubricated with Newtonian fluids.